If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -5 = 3x Reorder the terms: -5 + -4x = 3x Solving -5 + -4x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + -4x + -3x = 3x + -3x Combine like terms: -4x + -3x = -7x -5 + -7x = 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -7x = 0 Add '5' to each side of the equation. -5 + 5 + -7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = 0 + 5 -7x = 0 + 5 Combine like terms: 0 + 5 = 5 -7x = 5 Divide each side by '-7'. x = -0.7142857143 Simplifying x = -0.7142857143
| -2(5+6m)+19=-90 | | 5x^9+60x^8+135x^7= | | 2x^2-9x=-4 | | 2x^2-2x=8 | | 12x^3-20x^2+8x= | | 10x^4+13x^3-3x^2=0 | | 22x+12=-8x^2 | | Y=30-0.2x | | 15y^3-20y^2-20y= | | 2x+y=1263 | | 35x+67=95 | | 5d-4d+6d+8-4d=0 | | 2a-x=3c | | n-3n=25n | | 456c/5=10 | | 4v*3=35 | | 4v*3=45 | | 2*3*5/6=24 | | 3y=9-2x | | 5-11t=(5-2t) | | 5-11t=5(3x+8) | | 3y=9-2y | | 8x+3=-4x^2 | | -3x=-2x^2+2 | | 7-y=3x | | 2x^2-11x=-3 | | -4y+7=35y+6 | | -2x=-4x^2+2 | | -15-(-27v)=25+7v | | 4x^2+9x=2 | | -2x=-8x+3 | | 8k+24=12k-4 |